Atomically dispersed hierarchically ordered porous Fe–N–C electrocatalyst for high performance electrocatalytic oxygen reduction in Zn-Air battery. (May 2020) - Zhang, Xibo; Han, Xiao; Jiang, Zhe; Xu, Jie; Chen, Luning; Xue, Yakun; Nie, Anmin; Xie, Zhaoxiong; Kuang, Qin; Zheng, Lansun
Abstract: Rational design and synthesis of non-precious metal electrocatalysts for highly efficient oxygen reduction reaction (ORR) is urgently required. Recently, single atom catalysts (SACs) have sparked intense interests due to their maximum atom utilization efficiency and excellent properties in electrocatalysis. Herein, we reported an efficient ORR electrocatalyst with atomically dispersed FeN4 sites anchored on 3D hierarchically ordered microporous-mesoporous-macroporous nitrogen doped carbon (3DOM Fe–N–C). Owing to the synergism of highly dispersed FeN4 active sites and 3D hierarchically ordered porous architecture, 3DOM Fe–N–C-900, which was obtained via pyrolysis of ferrocene-encapsulated macro-microporous ZIF-8 precursor at 900 °C, exhibited an outstanding ORR activity in both alkaline ( E 1/2 of 0.875 V) and acid mediums ( E 1/2 of 0.784 V), as well as superior stability (only changed 2 mV after 10, 000 cycles in alkaline medium). Moreover, 3DOM Fe–N–C-900 as ORR catalyst in zinc-air battery achieved a high power density of 235 mW cm −2 and a high specific capacity of 768.3 mAh g −1, exceeding that driven by Pt/C. Our results revealed that the 3D hierarchically porous architecture of electrocatalysts could facilitate mass transport and increase the accessibility of active sites, thus optimizing their performances in ORR. This work well demonstrated the importance of rationally engineering porous structure of the catalyst for highly efficient ORR. Graphical abstract: Atomically dispersed hierarchically ordered porous Fe–N–C electrocatalyst (3DOM Fe–N–C) with superior oxygen reduction reaction activity and stability was successfully constructed by pyrolysis of porous macro-microporous MOF precursor at high temperature. Abundant atomically FeN4 sites and unique 3D ordered hierarchically porous architecture synergistically contribute to the high activity for ORR in zinc-air battery. Image 1 Highlights: Atomically dispersed FeN4 moieties were anchored in 3D hierarchically ordered N-doped carbon (3DOM Fe–N–C). Unique hierarchically ordered architecture effectively promoted mass transport and sufficient exposure of active sites. The catalyst exhibited a superior ORR activity in both alkaline and acid mediums to commercial Pt/C. Zn-air battery based on 3DOM Fe–N–C-900 exhibited a high power density (235 mW cm −2 ), exceeding that driven by Pt/C.